House prices and credit as transmission channels of monetary policy to inequality: evidence from OECD countries - Vale, S. (16th Annual Meeting of The Portuguese Economic Journal, 2023)
Using a panel vector autoregressive model this paper assesses the impact of monetary policy on the Gini coefficient of disposable income for 30 OECD countries between 1995Q1 and 2019Q4. We assume house prices and household credit as transmission channels, representing households’ financial balance. To capture the effect of the financial crisis the analysis further distinguishes the period that starts in 2008Q4. We find that a contractionary monetary policy increases the Gini coefficient in a moderate way. For the entire period, house prices are an effective transmission channel, a positive shock decreasing inequality, while credit is not statistically significant. Following the crisis credit stands out as the transmission mechanism, a positive credit shock reducing the Gini coefficient, while house prices lose relevance. These results are robust to different model specifications.